2018
DOI: 10.1002/ijc.31945
|View full text |Cite
|
Sign up to set email alerts
|

exSSSRs (extracellular S100 soil sensor receptors)‐Fc fusion proteins work as prominent decoys to S100A8/A9‐induced lung tropic cancer metastasis

Abstract: Within the “seed and soil” theory of organ tropic cancer metastasis is a growing compilation of evidence that S100A8/A9 functions as a soil signal that attracts cancer cells to certain organs, which prove beneficial to their growth. S100A8/A9‐sensing receptors including Toll‐like receptor 4 (TLR4), advanced glycation end products (RAGE), and also important receptors we recently succeeded in identifying (EMMPRIN, NPTNβ, MCAM, and ALCAM) have the potential to become promising therapeutic targets. In our study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…162 Thus, it has been recognized that S100A8/A9 plays a critical role in lung tropic metastasis and the subsequent growth of cancer cells in the lungs. 26,178 During metastasis, lung S100A8/A9 might act as a guiding protein for cancer cells that possess high expression levels of CD146. 162 In 2016, Ruma et al revealed that S100A8/A9 uses CD146 as a receptor during lung-specific metastasis of melanoma cells.…”
Section: Galectin-3mentioning
confidence: 99%
“…162 Thus, it has been recognized that S100A8/A9 plays a critical role in lung tropic metastasis and the subsequent growth of cancer cells in the lungs. 26,178 During metastasis, lung S100A8/A9 might act as a guiding protein for cancer cells that possess high expression levels of CD146. 162 In 2016, Ruma et al revealed that S100A8/A9 uses CD146 as a receptor during lung-specific metastasis of melanoma cells.…”
Section: Galectin-3mentioning
confidence: 99%
“…This study suggested that S100A8/A9 had the ability to attract melanoma cells to the lungs through the activation of RAGE. In a more recent study, the role of S100A8/A9 as a lung attractant for melanoma metastases was confirmed [163]. In this study, the authors showed that a neutralizing antibody against S100A8/A9 could reduce the formation of melanoma metastases in the lungs of mice [163].…”
Section: S100a8/a9mentioning
confidence: 58%
“…In a more recent study, the role of S100A8/A9 as a lung attractant for melanoma metastases was confirmed [163]. In this study, the authors showed that a neutralizing antibody against S100A8/A9 could reduce the formation of melanoma metastases in the lungs of mice [163]. S100A8/A9 has also been proposed to be a prognostic marker for metastasis, as well as a predictor of survival and determinant of therapeutic response in melanoma patients [164].…”
Section: S100a8/a9mentioning
confidence: 61%
“…The extracellular domain of CLEC-1A (exCLEC-1A)-Fc fusion protein was prepared from its corresponding conditioned media from cultures of a FreeStyle™ CHO-S cell (Chinese hamster ovary cell subline; Thermo Fisher Scientific)-derived stable clone. The stably expressed clone for exCLEC-1A-Fc was established by a convenient electroporation gene delivery method using our original pSAKA-1B vector as described (Kinoshita et al, 2019). After the collection of the serumfree conditioned medium from a large-scale culture of the established CHO cell clone, recombinant exCLEC-1A-Fc protein was purified by protein-G affinity chromatography according to the manufacturer's instructions.…”
Section: Surface Plasmon Resonance Analysis (Biacore)mentioning
confidence: 99%